Curriculum Integration Management in Islamic Education: A Case Study of Kerinci Modern Boarding School - Herningrum, Indah; Siregar, Anggi Desviana (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
This study aims to explore the integration of religious and general education in the curriculum development of modern Islamic boarding schools in Kerinci, Indonesia. Interviews, observations, and document analysis were used to gather information from curriculum managers, staff, and teachers using a descriptive qualitative approach and a thorough case study method. The findings reveal that both Arafah and Nurul Haq Islamic boarding schools implement integrated curricula to balance Islamic and secular education. Arafah applies an interdisciplinary approach that connects religious and general subjects, while Nurul Haq uses a multidisciplinary model that embeds Islamic values across subjects. Government policies support these integration efforts and aim to equip students with strong religious foundations and practical life skills. In conclusion, the integration of curricula in these institutions reflects efforts to maintain the relevance of Islamic education in modern contexts. This suggests that such models can be replicated in similar educational settings seeking to harmonize faith and modernity.